Countering Hybrid Threats: Challenges and the Role of Defense Science - Sarjito, Aris (Policy, Law and Political Research Center, 2024)
This study examines hybrid threats' evolution, national security implications, and defense science's role in countering and strengthening defense capabilities using secondary data analysis. The research aims to identify key trends and strategies for countering hybrid threats effectively, with a focus on the role of defense science in enhancing national defense capabilities. Qualitative research methods are employed to analyze existing literature and case studies on hybrid threats and defense science contributions. Findings suggest that hybrid threats have evolved significantly in the contemporary security landscape, necessitating adaptive and innovative defense strategies. Defense science plays a critical role in developing advanced technologies and methodologies to counter hybrid threats, including cybersecurity measures, information warfare tactics, and strategic communication strategies. Recommendations are provided for policymakers and defense practitioners to strengthen defense capabilities and mitigate the challenges of hybrid warfare, emphasizing the importance of interdisciplinary collaboration, international cooperation, and human capital development. In conclusion, the study underscores the importance of integrating insights from defense science into defense planning and preparedness efforts to effectively counter hybrid threats and safeguard national security.